PENENTUAN KOMODITAS UNGGULAN TANAMAN BAHAN MAKANAN LAHAN BUKAN SAWAH MELALUI PENDEKATAN OVOP DI KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Fauzi Nur Dewangga; Raden Hanung Ismono; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims at determining the most important criteria in supporting the development of One Village One Product (OVOP) products and identifying the competitive as food crop commodities developed in OVOP.  The researh was conducted in Astomulyo Village, Punggur Sub-district, Central Lampung District.  The research sites were selected purposively with consideration of the size of nonrice land for food crops is very high.  Respondents were determined purposively with expert judgement such as: food crop farmers, Agricultural Extensions, offficials of Horticulture/Agriculture Department, and business people.  Data were collected with FGD (Focus Group Discussion) and analyzed using AHP (Analysis Hierarchy Process).  The study shows that the most important criteria in supporting OVOP product development is capital aspect with the highest weight value of 44.65%, followed by economic aspect 24.83%, appearance and product quality aspect 13.76%, cultural and product specificity aspect 11.43%,, and physical and environmental carrying capacity aspect 5.33%. Pineapple is the best alternative crop with weighted of 44%, followed by corn 22%, cassava 16.8%, eggplant 10.7% and cucumber 6.1%. Key words:  decision making, OVOP, superior commodity